Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jad.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of distinct profiles of Posttraumatic Stress Disorder (PTSD) and Complex Posttraumatic Stress Disorder (CPTSD) based on the new ICD-11 Trauma Questionnaire (ICD-TQ)

Abstract: CPTSD is highly prevalent in treatment seeking populations who have been multiply traumatised in childhood and adulthood and appropriate interventions should now be developed to aid recovery from this debilitating condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
246
5
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(318 citation statements)
references
References 34 publications
41
246
5
9
Order By: Relevance
“…This finding is consistent with the existing literature, which found low symptoms as well as distinct classes of PTSD and cPTSD (e.g. Karatzias et al, 2017; Murphy et al, 2016). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with the existing literature, which found low symptoms as well as distinct classes of PTSD and cPTSD (e.g. Karatzias et al, 2017; Murphy et al, 2016). …”
Section: Discussionsupporting
confidence: 93%
“…Cloitre et al, 2013; Elklit, Hyland, & Shevlin, 2014). Other studies found support for two- or four-class solutions (Karatzias et al, 2017; Knefel et al, 2015). …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A PTSD diagnosis requires a score of ≥ 2 (‘moderately’) for at least one symptom in each of the three dimensions. The ITQ showed good psychometric properties in initial evaluations (Karatzias et al, 2016, 2017; Cronbach’s α  = .84 in this study). We used the mean scores of the dimensions for the scale-level analysis.…”
Section: Methodssupporting
confidence: 50%
“…Those who experience repeated interpersonal trauma, such as sexual and domestic violence, and abuse in childhood often present with PTSD with more complex features (Karatzias et al, 2017; Powers et al, 2017) than individuals exposed to single-incident traumas (Herman, 1997). Proposed diagnostic criteria for Complex PTSD (CPTSD) in the ICD-11 (due to be published in 2018) include the defining criteria of PTSD (re-experiencing, avoidance, numbing, and hyperarousal), in addition to the presence of at least one symptom in each of three self-organization features: affect dysregulation, negative self-concept, and interpersonal disturbance.…”
Section: Introductionmentioning
confidence: 99%